BANKING GOVERNANCE AND ITS IMPACT ON THE LEVEL OF BANKING PERFORMANCE: ISLAMIC BANK OF THE SOUTH/BABYLON - A MODEL - Ghadeer Hamed Shaker; Haider Jawad Kazem; Hanin Sami Hadi (Scholars Digest Publishing, 2024)
The aim of this research is to show the extent of the sample members' awareness of bank governance, to identify the approaches to evaluate the banking performance, and to depict the relationship of the correlation and influence among the research variables. The researchers adopted the descriptive analysis approach in this research and used the questionnaire as a tool for collecting data. The data was analyzed using the Social Statistics Program (SPSS). The research reached a set of conclusions, the most important of which are: There is a statistically significant correlation between the banking governance and the banking performance, as well as an impact of banking governance on the banking performance.
Keywords: Governance, Banking governance, Performance, Banking performance, Evaluation.